Inverse electron-demand Diels-Alder reactions for the selective and efficient labeling of RNA - Schoch, Juliane; Ameta, Sandeep; Jäschke, Andres (Chemical communications, 2011)
We report the first example of RNA labeling based on inverse electron-demand Diels-Alder reactions. Both chemically synthesized and enzymatically transcribed RNAs were successfully modified with biotin or a fluorescent label. This approach works efficiently under mild conditions in water and does not require transition metals.